Dermatophytoses in Prague, Czech Republic, between 1987 and 1998 - Kuklová, I; Kucerová, H (Mycoses, 2001)
Over a 12-year period, from 1987 to 1998, the spectrum of aetiological agents isolated from 11208 patients (6265 females and 4943 males) suspected of having dermatomycosis was analysed in the mycological laboratory of the Department of Dermatology, Charles University, Prague. The most frequently examined locations were toenails (34.9%), feet (15.6%), fingernails (12.8%), toe webs (11%), trunk (10%) and hands (8.7%). Dermatophytes were isolated from 5605 (30.2%) of all 18528 samples examined. Among dermatophytes, the most common infectious agent was Trichophyton rubrum (90.2%) followed by Trichophyton mentagrophytes (6.6%), Microsporum canis (1.8%) and Epidermophyton floccosum (1.4%). Trichophyton verrucosum, Microsporum persicolor and Microsporum gypseum were rare. During this 12-year period the pattern of aetiological agents of dermatomycoses in Prague was relatively stable.
Keywords: mitosporické houby; Mitosporic Fungi; mužské pohlaví; ženské pohlaví; dermatomykózy; incidence; Dermatomycoses; Humans; Female; Czech Republic; Incidence; lidé; Male; Česká republika